2009
DOI: 10.1128/ec.00305-08
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Mucin Antigens CpMuc4 and CpMuc5 Are Integral toCryptosporidium parvumInfection In Vitro

Abstract: Cryptosporidium, a waterborne enteric parasite, is a frequent cause of diarrheal disease outbreaks worldwide. Thus far, the few antigens shown to be important for attachment to and invasion of the host cell by Cryptosporidium are all mucin-like glycoproteins. In order to investigate other antigens that could be important for Cryptosporidium host-parasite interactions, the Cryptosporidium genome databases were mined for other mucinlike genes. A single locus of seven small mucin sequences was identified on chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 51 publications
2
73
0
1
Order By: Relevance
“…The finding that these sequences clustered separately from the other C. parvum sequences is interesting and consistent with those of previous studies, which showed that they are divergent at other loci including that of the gp40/15 (also called gp60) 41 and Muc4 genes. 44 Although most children in our study were infected with different C. hominis subtype families, 47 the finding that they developed significant antibody responses to the C. parvum antigen is consistent with that reported by Priest and others. 31 The results from both studies suggest that these responses are directed at epitopes conserved among species and different subtype families.…”
Section: P23 Antibodies and Polymorphisms In Children With Cryptosporsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding that these sequences clustered separately from the other C. parvum sequences is interesting and consistent with those of previous studies, which showed that they are divergent at other loci including that of the gp40/15 (also called gp60) 41 and Muc4 genes. 44 Although most children in our study were infected with different C. hominis subtype families, 47 the finding that they developed significant antibody responses to the C. parvum antigen is consistent with that reported by Priest and others. 31 The results from both studies suggest that these responses are directed at epitopes conserved among species and different subtype families.…”
Section: P23 Antibodies and Polymorphisms In Children With Cryptosporsupporting
confidence: 90%
“…41 Most human infections, particularly in resource-poor countries, are caused by C. hominis. Genes encoding other surface-associated Cryptosporidium proteins including gp40 42,43 and Muc4 and 5 44 are highly polymorphic among clinical isolates of different species and subtypes. If p23 is to be considered as a vaccine candidate, it is essential to investigate polymorphisms in the gene that encodes it among clinical isolates in different geographic areas.…”
Section: Introductionmentioning
confidence: 99%
“…gp900, gp40, gp15, Cpa135, Cp2, P23, and TRAP-C1 (Table 2) have or are predicted to have mucin-type O-glycosylation, suggesting that this type of posttranslational modification is common in proteins involved in attachment and invasion (133). Because mucin-like proteins were shown to be important for host-parasite interactions for Cryptosporidium, O'Connor and colleagues (193) undertook data mining of the Cryptosporidium genome databases to identify other mucin-like genes. They discovered a single locus of seven small mucin sequences (CpMuc1 to CpMuc7), which were expressed throughout the intracellular development stages.…”
Section: Adherence Factorsmentioning
confidence: 99%
“…Third, we may only be detecting the most abundant C. parvum glycoproteins, which include gp900 and gp40/gp15 (30,32). Indeed other recently characterized C. parvum mucins (C. parvum mucin 4 [CpMuc4] and CpMuc5), which are important for infectivity, are absent from the MPA affinity-purified proteins (25).…”
Section: Vol 9 2010mentioning
confidence: 99%
“…C. parvum sporozoites have on their surface unique mucin-like glycoproteins, which contain Serand Thr-rich repeats that are polymorphic and may be modified by O-linked GalNAc (4-7, 21, 25, 26, 30, 32, 34, 35, 43, 45). These C. parvum mucins, which are highly immunogenic and are potentially important vaccine candidates, include gp900 and gp40/gp15 (4,6,7,25,26). gp40/gp15 is cleaved by furin-like proteases into two peptides (gp40 and gp15), each of which is antigenic (42).…”
mentioning
confidence: 99%